LINGUISTIC REALITIES AND PECULIARITIES OF THEIR TRANSLATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article provides a definition of the term «realism» based on the works of linguists and scholars, and examines the types of realism. Examples of the connections between realisms in different languages are also presented. Additionally, the article discusses the features of translating realisms in literary texts.
Keywords: realia, culture, linguoculture, imagery of words, emotionality in text, translation features, expressive words